Dentatin Induces Apoptosis in Prostate Cancer Cells via Bcl-2, Bcl-xL, Survivin Downregulation, Caspase-9, -3/7 Activation, and NF-κB Inhibition. (3rd October 2012) - Arbab, Ismail Adam; Looi, Chung Yeng; Abdul, Ahmad Bustamam; Cheah, Foo Kit; Wong, Won Fen; Sukari, Mohd Aspollah; Abdullah, Rasedee; Mohan, Syam; Syam, Suvitha; Arya, Aditya; Mohamed Elhassan Taha, Manal; Muharram, Bushra; et al.
Abstract : This study was set to investigate antiproliferative potential of dentatin (a natural coumarin isolated from Clausena excavata Burm. F) against prostate cancer and to delineate the underlying mechanism of action. Treatment with dentatin dose-dependently inhibited cell growth of PC-3 and LNCaP prostate cancer cell lines, whereas it showed less cytotoxic effects on normal prostate epithelial cell line (RWPE-1). The inhibitory effect of dentatin on prostate cancer cell growth was due to induction of apoptosis as evidenced by Annexin V staining and cell shrinkage. We found that dentatin-mediated accumulation of reactive oxygen species (ROS) and downregulated expression levels of antiapoptotic molecules (Bcl-2, Bcl-xL, and Survivin), leading to disruption of mitochondrial membrane potential (MMP), cell membrane permeability, and release of cytochrome c from the mitochondria into the cytosol. These effects were associated with induction of caspase-9, -3/7 activities, and subsequent DNA fragmentation. In addition, we found that dentatin inhibited TNF- α -induced nuclear translocation of p65, suggesting dentatin as a potential NF- κ B inhibitor. Thus, we suggest that dentatin may have therapeutic value in prostate cancer treatment worthy of further development.